Implementation of Bribes (Risywah) Based on Law No. 20 of 2001 on Action Criminal Corruption in Legal Perspective Islam in Medan State Court - Ahmad Fadhly Roza; Mhd . Yadi Harahap; Ramadan Syahmedi Siregar (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
In accordance with the characteristics of empirical legal research using secondary data and the approach to this research is taken from legislation and revelation. Then the instrument used in this study is the cluster technique or called area sampling and interviews. The results showed; First, that there are too many statutory arrangements relating to bribery from time to time, there is no significant change from the description of the articles, it's just that the threat of punishment is getting heavier, and even overlaps with each other. Second, that the Medan District Court basically in adjudicating and deciding cases of bribery in corruption cases have used the prevailing laws and regulations, namely Law no. 31 of 1999 concerning the Eradication of Corruption Crime as amended by Law no. 20 of 2001 concerning Amendments to Law no. 31 of 1999 concerning the Eradication of Corruption Crime, however in applying the articles against the defendant still using a subjective interpretation. Third, that the responsibility for a criminal act only refers to prohibition and threatening of an act with a crime, whether the person who commits the act is then sentenced to punishment, this depends on whether in doing this act he has an error ( Geen straf zonder schuld; Actus non facit reum nisi mens sist rea ). This principle is not stated in written law but in unwritten law which also applies in Indonesia. The fiscal criminal law does not use mistakes. In fiscal punishment, if a person has violated the provisions, then he will be given a fine and confiscation. Corruption Crime Court. Whereas criminal responsibility for corruption perpetrators in the perspective of Islamic law is a lot of expert opinions, some are proposing cutting off hands, ta'zir , imprisonment and even the death penalty due to criminal acts of corruption which relies on syariqoh, ghulul , risywah and so on.